(untitled) (Journal of actual problems of jurisprudence, 2016)
This article describes the control levers contractual relations develop in parallel with the nomadic way of life of the Kazakh society . Resulting thoughts and attitudes of many scientists researchers discovers reasons for the formation of contractual relations and norms governing their . And also describes sources of norms in managing contractual relationships such as purchase and sale , exchange or other domestic relations . As a result, the characteristics of individual sources Kazakh customary law derived types of contractual relations . And of course the interpretation of customary law in the light of dan made it possible to make your own conclusion.